Ocean submesoscales as a key component of the global heat budget - Zhan Su (Nature Portfolio, 2018)
Oceanic motions associated with horizontal scales smaller than 50 km remain unresolved in climate models. Here the authors show that motions in this scale range are critical to the global transport of heat between the ocean interior and the atmosphere, and are thus a key component of the Earth’s climate.